2015
DOI: 10.1002/jsc.2001
|View full text |Cite
|
Sign up to set email alerts
|

Crop Microinsurance for Maize Farmers in Burkina Faso: Access and Agriculture Performance in the Dandé Village

Abstract: Crop insurance in the Sahel improves the access of insured farmers to resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
(43 reference statements)
1
8
0
2
Order By: Relevance
“…Some of the merits of index-based crop insurance are: (i) it minimizes the longstanding contract problems such as moral hazard/hidden action and adverse selection/ hidden information as the index read from weather stations is exogenous and cannot be tampered with the intervention of participating farmers (Barnett and Mahul 2007;Barnett et al 2007;Devereux and Guenther 2009); (ii) in the case of crop damage, it makes faster payouts, which means that farmers will not have to sell assets or depend on emergency food aid to survive during climate shocks (CCAFS 2014); (iii) insured households are more likely to invest on agricultural inputs leading to higher outputs and income per unit of land (Sundar and Ramakrishnan 2013); and (iv) it enhances farmers' ability to withstand and recover from adversity, therefore strengthening resilience of communities as well as assisting them to get out of the vicious circle of poverty and improve household welfare (World Bank 2005;Berg et al 2009; De Bock and Gelade 2012;Koloma 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the merits of index-based crop insurance are: (i) it minimizes the longstanding contract problems such as moral hazard/hidden action and adverse selection/ hidden information as the index read from weather stations is exogenous and cannot be tampered with the intervention of participating farmers (Barnett and Mahul 2007;Barnett et al 2007;Devereux and Guenther 2009); (ii) in the case of crop damage, it makes faster payouts, which means that farmers will not have to sell assets or depend on emergency food aid to survive during climate shocks (CCAFS 2014); (iii) insured households are more likely to invest on agricultural inputs leading to higher outputs and income per unit of land (Sundar and Ramakrishnan 2013); and (iv) it enhances farmers' ability to withstand and recover from adversity, therefore strengthening resilience of communities as well as assisting them to get out of the vicious circle of poverty and improve household welfare (World Bank 2005;Berg et al 2009; De Bock and Gelade 2012;Koloma 2015).…”
mentioning
confidence: 99%
“…For example, in Burkina Faso, it has been observed that less than 10% of farmers have fully enrolled in the ongoing pilot initiatives. Although no consensus has emerged as to why this is so, some of the possible reasons advanced by many crop insurance experts include: (i) difficulties in dealing with climate features, particularly the problem of huge spatiotemporal rainfall variability, which is often used as weather-based index for designing pilots-also called spatial basic risk (Berg et al 2009;Ibrahim et al 2014;Fonta et al 2017); (ii) difficulty to solve the trade-offs between level of protection and cost of insurance premium (Berg et al 2009;Muller 2012;Koloma 2015); (iii) lack of stakeholders involvement in analyzing insurance products and policies (van Asseldonk et al 2013;Muller 2012); (iv) poor understanding of the concept of crop insurance, inability to pay premiums, as well as rigid enrolment criteria (van Asseldonk et al 2013; Planet Guarantee 2014); (v) uncertainty in cash flows as many banks and large microfinance institutions (MFIs) are very reluctant to finance agriculture through small microfinance institutions (MFIs) and cooperatives (Koloma 2015; Planet Guarantee 2015); and finally, (vi) poor understanding of famers' risk perception in general, their willingness to pay, and the factors that influence their decision to pay such as low level of trust in insurance providers.…”
mentioning
confidence: 99%
“…The impact could be social such as gender or poverty alleviation, and indeed find a positive impact (Bansal & Singh, 2020; Koloma & Alia, 2014; Sinha, 2015). Others find that microinsurance leads to more agricultural production by insured farmers (Banerjee et al, 2014; Koloma, 2015). Others find that microfinance institutions lend only to educated people with experience who can bring in their own equity (Koubâa, 2014).…”
Section: Research Directionsmentioning
confidence: 99%
“…These studies used the logit regression method (Abraham Falola, Opeyemi Eyitayo Ayinde, and Babatola Olasunkanmi Agboola, 2018). Probit is to identify factors According to (Koloma, Y, 2015), (Okoffo, E.D., Denkyirah, E.K., Adu, D.T. et al, 2016), the area factor negatively affected the willingness to participate in agricultural insurance.…”
Section: Literature Reviewmentioning
confidence: 99%